Functional movement screen: inter-rater and subject reliability. Issue 4 (27th March 2011) - Shultz, R; Mooney, K; Anderson, S; Marcello, B; Garza, D; Matheson, G O; Besier, T
Abstract : Background: A screening test evaluates a functional movement by assessing an athlete's functional limitations, weaknesses, or impairments that may increase the risk of injury for the athlete. Objective: To assess the inter-rater reliability and subject variability of the Functional Movement Screen (FMS) and to analyze the use of video scoring as opposed to live scoring. Design: A reliability study. Each athlete was tested and retested, 1 week apart by the same rater, who also scored the athlete's first session from a video recording. These video recordings were then scored by five other raters. Setting: Human Performance Lab using two standard video cameras (sagittal and frontal views) and SiliconCoach video capture software. Participants: 21 female (19.6±1.5 years, 64.4±5.1 kg, 1.7±0.1 m) and 19 male (19.7± 1.0 years, 80.1 ±9.9 kg, 1.9±0.1 m) Varsity athletes from swimming, soccer, volleyball, cross-country and gymnastics volunteered to participate, along with six raters. Assessment: The FMS consists of seven tasks that focus on mobility and stability. Each task is rated out of 3, with pain being an automatic zero, for a total score out of 21. Raters (6) looked for malalignment and asymmetry. Main outcome measurement: The Krippendorff alpha (Kalpha) was used to assess the reliability of each of the three tests: inter-rater, test-retest, live versus video. Results: The Kalpha for the inter-rater, the test-retest, and the live/video was 0.3806, 0.6161, and 0.9096, respectively. Conclusion: Inter-rater reliability results show that clinicians should avoid comparison across multiple raters. It is possible that with more training this value may increase. Fortunately, if a single rater is used, clinicians can be confident that a change in the FMS score is due to a change in the athlete as the test-retest produced good reliability. This study also demonstrates that streamlining the FMS process with the use of video capture is appropriate.